Psychosocial and environmental correlates of cycling for transportation in Brussels. (May 2019) - de Geus, B.; Wuytens, N.; Deliens, T.; Keserü, I.; Macharis, C.; Meeusen, R.
Abstract: This study examines which psychosocial and environmental factors are associated with cycling in the Brussels Capital Region (BCR) and whether these associations differ between those who never cycle for transport purposes (Non-cyclists) and those who used the bicycle at least once a week in the previous 6 months (Cyclists). Adults (18–65 year; N = 503; 47% women) living and/or working in the BCR completed an online questionnaire assessing socio-demographic, general transport, psychosocial and environmental variables. Psychosocial factors were significantly different (p < 0.001) between Cyclists and Non-cyclists, with Cyclists having a higher score for Modelling, Social support and perceiving more Benefits. The physical environmental factors were not significantly different between the Cyclists and Non-cyclists. Cyclists indicate more often that cycling is unpleasant because of the exhaust fumes and pressure from motorized traffic. The likelihood of a woman being a Cyclist is 1.61 times smaller compared to a man being a Cyclist. The influence of individual and social factors seems to be more predictive in distinguishing between Cyclists and Non-cyclists.